Gender-Based Crimes in South Korea: Threats to Women's Safety in The Implementation of Cedaw - Imaniar Insy Savety Habibah (Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
Gender inequality in South Korea remains a persistent issue, marked by increasing gender-based violence in both physical and digital spaces. Rising cases of femicide, sexual violence, and digital exploitation, such as the discovery of a deepfake chatroom involving more than 220,000 male members, have heightened women’s sense of insecurity in everyday life. This study aims to examine gender-based violence as a threat to women’s human security in South Korea and to evaluate the state’s implementation of the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) through a feminist analytical framework. Using a descriptive qualitative method based on secondary data, the research applies Feminist Security Theory (FST) to shift the concept of security beyond state-centric and military perspectives toward individual well-being and freedom from fear. The findings indicate that despite South Korea’s formal ratification of CEDAW, entrenched patriarchal norms, institutional bias, and weak legal enforcement continue to undermine women’s security. Gender-based violence is frequently normalized or inadequately addressed, revealing a significant gap between international commitments and domestic practice. Furthermore, the analysis shows that the emergence of the 4B Movement, Bihon, Bichulsan, Biyeonae, and Bisekseu, represents a collective response to state failure in ensuring women’s safety. The movement reflects women’s loss of trust in legal and social institutions and highlights how women reclaim agency through resistance. This study concludes that effective implementation of CEDAW requires structural transformation of social, cultural, and institutional frameworks that perpetuate gendered insecurity.